Evaluation of the status of water quality of three swimming pools in Bujumbura city, Burundi - Niyungeko, Christophe; Ntirampeba, Jonas; Bararunyeretse, Prudence; Tiimub, Benjamin Makimilua; Nihorimbere, Manassé; Ntakiyiruta, Pierre (International Journal of Environment, 2022)
Poor water quality is problematic for the health of public swimmers. This study focused on the water quality of three main swimming pools coded as MS, ES and HC in the city of Bujumbura, Burundi. Water samples were collected from June to the end of August 2020 and analyzed for physicochemical parameters such as pH, turbidity, conductivity, nitrates, free chlorine and microbiological parameters (total coliforms and faecal coliforms). Our results indicated that 2/3 of the sampling days showed pH >7.8 and pH<7.2 in the MS and HC pools, respectively. All these pools exhibited high turbidity whereas ES manifested very high value (6.05NTU). Free chlorine appeared very low in the MS pool with contamination by total coliforms (<1MPN 1mL-1 and 1.17x107MPN 1mL-1, <1MPN 1mL-1 and 6.32x106MPN 1mL-1, and < 1MPN 1mL-1 and 5x102 MPN 1mL-1) for MS, ES, and HC respectively. Both MS and ES pools revealed higher thermotolerant coliforms contamination of (<1MPN 1mL-1 and 2.18x104MPN 1mL-1) in MS and (<1MPN 1mL-1 and 2.32x104MPN 1mL-1) in ES, but the HC pool showed a single contamination case with values of <1UFC 1mL-1 and 5UFC1mL-1 throughout the sampling period. Additionally, extreme concentrations of nitrates (104.89 mgL-1) were observed at the ES pool. The findings showed a non-compliance with WHO standards for all three swimming pools and therefore advocates for an urgent need to monitor and treat or change the water frequently for quality assurance of swimming pools.